Integrative Systems of Production: A framework and model for designers, based on ecosystem metabolisms and functions - Snow, Tom (FormAkademisk, 2020)
Different branches of design are shifting from a primary focus on artefacts as ends to concentrating on means (e.g. forms of production), with ends encompassing larger societal goals. Concurrently, humanity is facing an increasingly carbon-and-freshwater-constrained world, combined with escalating realities of climate change and ecosystem degradation; thus, our means of production must evolve. An integrative framework and model has been developed to support designers (and other stakeholders) working on regenerative systems of production. The model integrates synergistic, circular, cascading and aggregate efficiency design systems based on ecosystem concepts, as well as regenerative agriculture, the bioeconomy and the (technical) circular economy. With this integrative approach, stakeholders may develop more productive, regenerative synergies and hybrid activities that produce zero waste. The model can be applied at the micro-, meso- and macro-scales. Keywords: Systemic design, ecological design, biomimetics, circular economy, regenerative agriculture.